Impacto del sistema tributario actual sobre la pequeña minería en Sogamoso, Boyacá (2023)
Coal mining has gone through several phases, where the government in the last decade gave incentives to these practices so that families that depended on this activity had a means to survive, with the change of government and new policies the miners have obtained for returning to illegality mostly due to the increase in taxes without compensation from the government, such as access to decent roads and so on.